2007
DOI: 10.1086/520547
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2 Antibiotics That Inhibit Protein Synthesis for the Treatment of Infection withYersinia pestisDelivered by Aerosol in a Mouse Model of Pneumonic Plague

Abstract: Doxycycline behaves in vivo as a bacteriostatic drug, requiring an intact immune system for clearance of the infection after aerosol challenge with Y. pestis. Gentamicin is bactericidal, even when given on a daily schedule. Neutropenia did not significantly affect survivorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…in uninfected mice (not shown). The pharmacokinetics of doxycycline have been previously reported; 40 mg/kg administered twice a day (24-h total of 80 mg/kg) yielded an approximate 24-h AUC of 107 g · h/ml and was predicted to be efficacious based on successful outcomes in other infection models (18).…”
Section: Resultsmentioning
confidence: 99%
“…in uninfected mice (not shown). The pharmacokinetics of doxycycline have been previously reported; 40 mg/kg administered twice a day (24-h total of 80 mg/kg) yielded an approximate 24-h AUC of 107 g · h/ml and was predicted to be efficacious based on successful outcomes in other infection models (18).…”
Section: Resultsmentioning
confidence: 99%
“…The calculated inhaled dose for each mouse was 1.02 ϫ 10 6 CFU or 15 LD 50 . Doses in this range have been used previously for successful aerosol Y. pestis challenge (3,36,75).…”
Section: Resultsmentioning
confidence: 99%
“…Using controlled conditions, we showed that a subtherapeutic antimicrobial regimen in conjunction with AGPs provided nearly 100 % protection against a challenge with 200 LD 50 Y. pestis CO92. Currently, only streptomycin, tetracycline or doxycycline are approved by the United States Food and Drug Administration for treatment of plague, although it has been shown that gentamicin and levofloxacin are equally effective when given early to infected mice (Heine et al, 2007;Inglesby et al, 2000). Previous results demonstrate that aggressive gentamicin treatment at 12 mg (kg body weight)…”
Section: Discussionmentioning
confidence: 99%